Review: The Next Steps in Crop Improvement: Adoption of Emerging Strategies to Identify Bottlenecks in Sugar Flux. (December 2020) - Beuchat, Gabriel; Xue, Xueyi; Chen, Li-Qing
Highlights: Genetic engineering of sugar partitioning offers a promising yet challenging strategy to improve crop yields. Identifying dynamic bottlenecks in sugar flux can open up fruitful avenues to maximize crop yields. Four methodologies are discussed with applications for carbon allocation bottleneck characterization, especially under conditions of stress. Abstract: Sugar allocation in plants is the fundamental process that transports sugar from source to sink tissues and has a dramatic impact on crop yields. Controlling sugar allocation is required to increase crop yields, as well as biomass for biofuel production. Successful examples have demonstrated that genetic engineering of sugar partitioning offers a promising strategy to achieve this goal. However, improvement has thus far been limited by gaps in understanding of the underlying mechanisms controlling the allocation of sugars. The dynamics of sugar partitioning are minimally predictable under different conditions, between species, or in response to abiotic stresses. Here, we discuss four methodologies that have not been sufficiently exploited for the identification of bottlenecks in sugar flux. Furthermore, we suggest how these strategies can be used and combined to provide the insight needed to maximize crop yields or biomass, especially under conditions of environmental stress.